Tracking the invasion of Hemiramphus far and Saurida undosquamis along the southern Mediterranean coasts: A Local Ecological Knowledge study - BOUGHEDIR, W.; RIFI, M.; SHAKMAN, E.; MAYNOU, F.; GHANEM, R.; BEN SOUISSI, J.; AZZURRO, E. (Mediterranean Marine Science, 2015)
Local Ecological Knowledge of 92 professional fishers from Tunisia and Libya was used to investigate on the occurrence and establishment of the exotic Hemiramphus far and Saurida undosquamis along the southern Mediterranean coasts. According to fisherman’s knowledge, H. far and S. undosquamis appeared in Libya, in 1980 and 1989 respectively. In Tunisia these species were observed afterwards, in 2004 and 2007. Currently both H. far and S. undosquamis result to be well distributed and established, along the entire surveyed area, from Tubrouk (eastern Libya) to Tabarka (western Tunisia). A statistical analysis of the qualitative trends in abundance perceived by the respondents show that both species have significantly increased in abundance in Tunisia. In Libya an increase of the abundance of H. far was also apparent during the first decade of the 21st century but the current abundance of S. undosquamis resulted to be stable at the level of occasional captures. Given the lack of regular environmental monitoring programmes in the area, these findings provide information that could not have been obtained otherwise. Besides improving our understanding on the status and chronology of these invasions, this approach highlights the value of fisherman’s knowledge to reconstruct ecological process in the course of rapid historical modifications.